Cambridge primary English learner's book 4 - Burt, Sally (United kingdom : Cambridge university press, 2021)
Cambridge Primary English Learner$1 (Bs Book 4 is designed to help primary school students enhance their English language skills, focusing on reading, writing, speaking, and listening. The book provides a variety of engaging activities, stories, and exercises that support the development of grammar, vocabulary, and comprehension. It introduces more advanced language concepts in a child-friendly way, encouraging students to use English confidently in different contexts. With its clear explanations and structured approach, the book helps students build a solid foundation in English while fostering their creativity and communication skills.s
Keywords: English : Textbook